SAFFRON DREAMS-A JOURNEY OF EVOLVING IDENTITY - Majeed, Saima; Zaidi, Najia Asrar; Waheed, Dr. Zarina (Al-Burz, 2017)
Saffron Dreams is a tale of a woman set in the immigrant milieu. It narrates how resolve and resistance can cope with hatred and weakness could harness indigenous strength against othering. The novel vividly portrays how distinct identities vanish, rebirth and evolve amidst the challenges; challenges that threaten lives and existence. It describes the epic struggle of a Pakistani woman, coming from a conservative society, whose dreams die. The research explores the evolving identity of the protagonist; the subject matter of identity is discussed with theoretical background. The Analysis revolves round Arissa who after sudden collapse of marital bliss is pushed to edges by society. The powerful longing for a renewed identity helps Arrisa prepare to live at the cost of sacrificing her ‘hijab’ whom she thinks as a symbol of bondage with her deceased husband. The beholder lives on with new version of her dreams marked by the desires to come out of the clutches of ‘time’ on canvass of her life colored with uncertainties and fatigued compromises. The study is exploratory in purpose, following the content-based mode of analysis.